Involvement of OsRIP1, a ribosome-inactivating protein from rice, in plant defense against Nilaparvata lugens. (February 2020) - De Zaeytijd, Jeroen; Chen, Pengyu; Scheys, Freja; Subramanyam, Kondeti; Dubiel, Malgorzata; De Schutter, Kristof; Smagghe, Guy; Van Damme, Els JM.
Abstract: Rice is the most important staple food in the world, but rice production is challenged by several biotic stress factors like viruses, bacteria, fungi and pest insects. One of the most notorious pest insects is Nilaparvata lugens, commonly known as the brown planthopper, which feeds on rice phloem sap and can cause serious damage to rice fields. In order to protect themselves, plants express a wide array of defense proteins such as ribosome-inactivating proteins (RIPs). This study shows that the expression of 'OsRIP1' is highly induced in rice plants infested with N. lugens, with transcript levels more than 100-fold upregulated in infested plants compared to non-infested plants. Furthermore, recombinant OsRIP1 was toxic for brown planthoppers when administered through liquid artificial diet. OsRIP1 inactivated insect ribosomes in vitro, suggesting that its toxicity relates to the enzymatic activity of OsRIP1. Over-expression of OsRIP1 in transgenic rice plants did not affect the performance of insects reared on these plants, most likely due to insufficient concentrations of OsRIP1 in the phloem. The data obtained in this research indicate that OsRIP1 can play a role in plant defense against herbivorous insects. Graphical abstract: Image 1 Highlights: OsRIP1 expression in rice plants is triggered by Nilaparvata lugens infestation. Recombinant OsRIP1 is toxic for N. lugens when supplemented in artificial diet. Recombinant OsRIP1 interferes with N. lugens development. Recombinant OsRIP1 inhibits translation by insects ribosomes.